Membangun Keluarga Ramah Anak melalui Manajmen Pendidikan Keorangtuaan di Lingkungan Bermain - Arga Dwi Praditya; Sri Wahyu Nurhidayati; Gita Arra Hervina (Yayasan Mutiara Hati Moeslem, 2025)
This study aims to analyze the application of parental education management in building child-friendly families in the play environment at PAUD Peduli Anak, Suka Bandung Village, Pino Raya District, South Bengkulu Regency. The background of this study stems from an awareness of the importance of childhood as a golden age in shaping children's character and potential, in which the family plays a role as the first and foremost educational institution. However, the phenomenon of busy parents, lack of understanding of parenting patterns, and weak collaboration between home and school often become obstacles in creating a conducive educational environment. This study used a qualitative descriptive approach with a case study method. Data were collected through observation, in-depth interviews, and documentation, then analyzed using an interactive model that included data reduction, data presentation, and conclusion drawing. The results show that parenting education management at PAUD Peduli Anak is implemented through participatory planning, partnership strategies between teachers and parents (such as regular meetings, home visits, and participation in school activities), and collaborative evaluation-based supervision. Factors supporting the program's success include teacher motivation, support from institutions and education agencies, and parental readiness. The main obstacles include time constraints, the perception that education is solely the responsibility of teachers, and socioeconomic constraints. Overall, the implementation of the parenting program has a positive impact on children's social, emotional, and academic development, as well as increasing public trust in educational institutions.